Down syndrome with ambiguous genitalia: A rare association (Indian Journal of Case Reports, 2018)
Down syndrome (DS) is one of the most common chromosomal disorders. Although genitourinary anomalies, such as a cryptorchidism, micropenis, posterior urethral valves, and hypospadias, have been recognized as complications, the association of ambiguous genitalia with DS has been rarely reported. We report the case of a 1-year-old baby; assigned male sex at birth who was the first child born of a non-consanguineous marriage, by vaginal delivery at term with a birth weight of 2.2 kg. The baby had clinical features suggestive of DS with a micropenis, penoscrotal hypospadias, and incompletely fused labial-scrotal folds with palpable gonads. The external masculinization score was 3/12. The child was reared as a male and hormonal investigations were suggestive of androgen insensitivity. Karyotype was 47, XY, +21.